Crossing the Language and Culture Divide- The Challenges of Educating Asian Law Students in a Globalising World - Steven Freeland; Grace Li; Angus Young (Legal Education Review)
My journey as a law university teacher began in 1976 with my appointment as a part-time lecturer continuing uninterrupted to the present. Over these 28 years, I have journeyed both physically and intellectually. My journey has taken me from my homeland to an adopted country. I have also had cause to reflect upon and change my conceptions and practice of teaching. In this teaching note I share the beginnings of my academic career, my first teaching methods, and the developments that occurred in my teaching. I then describe my present philosophy and practice of teaching, using my first-year law course as an example. I present the evaluations of my teaching and the analysis that I have done of these appraisals. I conclude with the lessons drawn from my teaching journey. I have chosen to share this journey in the hope that this may be a source of inspiration for new academics and reassure more experienced academics who are committed to the cause of student-centred teaching and learning.